2019
DOI: 10.1016/j.vetmic.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The SPI-19 encoded type-six secretion-systems (T6SS) of Salmonella enterica serovars Gallinarum and Dublin play different roles during infection

Abstract: Salmonella Pathogenicity Islands 19 (SPI19) encodes a type VI secretion system (T6SS). SPI19 is only present in few serovars of S. enterica, including the host-adapted serovar S. Dublin and the host-specific serovar S. Gallinarum. The role of the SPI19 encoded T6SS in virulence in these serovar is not fully understood. Here we show that during infection of mice, a SPI19/T6SS deleted strain of S. Dublin 2229 was less virulent than the wild type strain after oral challenge, but not after IP challenge. The mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…T6SS systems in Salmonella are encoded from the horizontally acquired islands, SPI-6 or SPI-19 [60,61]. Reports have demonstrated that T6SS plays a role in Salmonella pathogenicity; SPI-19 plays a role in killing competing bacteria in the intestine [61,62], and it would be interesting to investigate the role of T6SS in S. Muenster, S. Chester and S. Aberdeen. Interestingly, three S. Isangi, S. Takoradi and S. Larochelle strains were identified to have virulence genes not possessed by the other strains in our study; virulence genes that have not been reported in these serotypes previously.…”
Section: Discussionmentioning
confidence: 99%
“…T6SS systems in Salmonella are encoded from the horizontally acquired islands, SPI-6 or SPI-19 [60,61]. Reports have demonstrated that T6SS plays a role in Salmonella pathogenicity; SPI-19 plays a role in killing competing bacteria in the intestine [61,62], and it would be interesting to investigate the role of T6SS in S. Muenster, S. Chester and S. Aberdeen. Interestingly, three S. Isangi, S. Takoradi and S. Larochelle strains were identified to have virulence genes not possessed by the other strains in our study; virulence genes that have not been reported in these serotypes previously.…”
Section: Discussionmentioning
confidence: 99%
“…Like other serovars that are frequently associated with invasive human disease, S . Choleraesuis encodes a T6SS, which plays a role in virulence in vivo (Schroll et al, 2019). S .…”
Section: Disease Diversity-nontyphoidal Salmonellosis Disease Severitmentioning
confidence: 99%
“…Variant analysis revealed several mutations in components involved in the Type VI secretion system (T6SS) of SPI-19 that plays a role in intestinal infection (Table 1) [39][40][41]. Homology between the contractile components of phages and T6SS of several Salmonella serovars that deliver cytotoxic effector proteins via spikes that enter the host cell was recently reported [42][43][44]. Many core structural components, however, have not been extensively characterized on a functional level [45].…”
Section: Adhesion and Invasion Assaysmentioning
confidence: 99%